Information and communication technology transform the agricultural extension practices in North Maluku, Indonesia - Sugihono, Chris; Hariadi, Sunarru Samsi; Wastutiningsih, Sri Peni (International Journal of Advances in Applied Sciences, 2025)
The world's swift digitization has profoundly transformed how farmers and extension workers operate, learn, and communicate. This study explores how information and communication technologies (ICT) adoption transforms agricultural extension practices in North Maluku, Indonesia. Using a qualitative approach, the study gathered and analyzed data from fifteen extension workers through interviews, observation, documentation, and focus group discussions from November 2022 to March 2023. The findings reveal ICT adoption has transformed the extension workers’ strategies in five areas: i) coordination and collaboration, ii) digital learning, iii) virtual group dynamics, iv) promotion and mobilization, and v) online consultation and monitoring. However, ICT adoption has not replaced traditional extension methods, such as demonstration plots, field schools, and field trips. The use of ICT is not always in line with the deterministic view that technology automatically changes society. In contrast, recursive patterns in practice adaptation create complex dynamics in which extension workers' decisions continue to play a key role in the evolution of agricultural extension. These findings enrich practical and policy debates regarding harnessing ICT potential for enhanced agricultural extension in Indonesia. Additionally, they advance theoretical discussions on the merits of the technological determinism perspective in analyzing ICT utilization.